Вміст іонів карбонатно-кальцієвої рівноважної системи в питних підземних водах Київської області - Калінін, І.В.; Богатиренко, В.А.; Біленко, М.А.; Нестеровський, В.А.; Євдокименко, В.О. (Доповіді НАН України, 2020)
Показано, що частота відхилення якості питної води водопроводів України від нормативних вимог є основною причиною того, що для населення України актуально використання підземних питних вод нецентралізованого водопостачання. Виявлено, що іонно-молекулярний склад підземних вод Київської області не
стабільний внаслідок тріщинуватості водотривких порід, що визначає якість підземних вод і умови їх використання населенням. Наведено результати вивчення вмісту основних компонентів іонно-молекулярного
складу системи карбонатно-кальцієвої рівноваги на прикладі підземних питних вод різного походження
західної частини Дніпровсько-Донецького артезіанського басейну (ДАБ) Київської області поблизу Києва.
Показано, що ці зміни взаємопов'язані з кліматичними умовами року та особливостями гідрогеологічного режиму ДАБ. Currently, the quality of water resources is becoming a factor that limits and regulates water use processes, and,
most of all, it relates to drinking water. Increasing frequency of deviations of the drinking water quality of
water supply systems of Ukraine from the regulatory requirements is the main reason for the use of underground
drinking water of non-centralized water supply for the population of Ukraine. Groundwater is usually more
protected from the effects of industrial and economic activities. The groundwater of the Kyiv region is represented
by the aquifer complex of the western part of the Dnieper-Donets artesian basin (DAB): the Quaternary
tier (at depths of 30—50 m), Kharkiv horizon (≈ 90 m), Buchach horizon (within 60—120 m depth), aquifer
the Cenomanian-Callovian horizons (120—160 m) and Middle Jurassic deposits. According to the hydrogeological
model, this artesian system is characterized by the intense vertical water exchange of mainly downward
filtration of gravitational groundwater due to the high fracture and permeability of separate weakly permeable
layers. Through pores and cracks, a considerable mass transfer of dissolved chemicals occurs, which
causes the variable cationic and anionic compositions of groundwater, as well as concentration fluctuations of
pore solutions. The surface water, whose quality is highly dependent on both climatic conditions and human
activity, gradually penetrate through a system of pores and cracks into the artesian basins of the DAB, creating
the prerequisites for their contamination. Accordingly, the monitoring of the state of groundwater within the
Kyiv region is necessary and should be permanent.
The results of experimental data on the groundwater quality, namely pH, total acidity, alkalinity, and content
of calcium and magnesium ions are obtained in the period April—October 2017. On their basis, the parameters
of the ionic molecular composition of the carbonate-calcium equilibrium system were calculated, as well as
the aggressiveness and stability of groundwater depending on the season — spring, summer, and autumn. It is
shown that the changes of the carbonate-calcium equilibrium in the groundwater system of the Kyiv region are
closely interconnected with the atmospheric precipitation and depend on the periods of seasonal fluctuations
of precipitation (maximum falls in April and October 2017), according to the State Geological Information
Fund of Ukraine on climate seasonal changes in 2017. In all aquifers during the periods of intense rainfall and
low temperatures, the content of free CO₂ increases, which is mainly included in the carbonate-calcium equilibrium
system. Fluctuations in the carbon dioxide content also correspond to seasonal changes in pH: the more
CO₂ is dissolved in water, the lower the pH.
In the dry season, the maximum content of CO₃²⁻ions in the water is observed, which, in turn, coincides
with the maximum value of the degree of saturation of SICaCO₃. Groundwater has a sufficiently high degree of
saturation of CaCO₃, the metastable nature of which is explained by the low concentrations of CO₃²⁻ anions
and the predominant amount of HCO₃ ions, provided that the pH fluctuates within pH = 6 ÷ 8. Upon reaching
the surface, such carbonates (sediments) are easily formed in such waters. Therefore, before use, groundwater
within the Kyiv region, the additional purification is needed to reduce the carbonate hardness of water. According
to the Langelier index, they are not corrosive. Показано, что частота отклонения качества питьевой воды водопроводов Украины от нормативных требований является основной причиной того, что для населения Украины актуально использование подземных питьевых вод нецентрализованного водоснабжения. Выявлено, что ионно-молекулярный состав
подземных вод Киевской области нестабилен вследствие трещиноватости водоустойчивых пород, что
определяет качество подземных вод и условия их использования населением. Представлены результаты изучения содержания основных компонентов ионно-молекулярного состава системы карбонатно-кальциевого равновесия на примере подземных питьевых вод различного происхождения западной части Днепровско-Донецкого артезианского бассейна (ДАБ) Киевской области вблизи Киева. Показано, что эти
изменения взаимосвязаны с климатическими условиями года и особенностями гидрогеологического режима ДАБ.